Safeguarding global health security amidst a scramble for Africa’s minerals for the clean energy transition - Oluwayemisi Ajumobi (Globalization and Health)
Abstract The global transition to renewable energy is increasing the demand for critical minerals mining in Africa. Without appropriate safeguards, expansion of mining operations on the continent increases the risk of mining-associated infectious disease outbreaks with epidemic and pandemic potential.